2017
DOI: 10.15294/kemas.v12i2.5970
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Surveillance of Malaria Vectors in Saumlaki, Maluku Tenggara Barat Regency, Maluku Province

Abstract: The research aims to determine the prevalence of malaria and Anopheles spp using bio-ecology surveillance in Alusi and Waturu community health centers in Maluku Tenggara Barat Regency. The study was conducted in March-April 2015 with cross sectional design. In this research, we performed mass blood survey on 489 participants in the Kilmasa village and 434 participants in Waturu village. We also performed entomology surveillances, i.e. larval density, catching Anopheles spp, temperature, humidity, and salinity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
2
0
4
Order By: Relevance
“…The Anophels farauti larva is the only species that able to live on all type of habitat, whether permanent or not, fresh water or brackish water. The research (Sandy et al, 2017) in Kelaan and Kilmasa, Maluku Tenggara Barat also found out Anophels farauti larva live on fresh water or brackish water habitat. While two other species only found on fresh water habitat.…”
Section: Resultsmentioning
confidence: 89%
“…The Anophels farauti larva is the only species that able to live on all type of habitat, whether permanent or not, fresh water or brackish water. The research (Sandy et al, 2017) in Kelaan and Kilmasa, Maluku Tenggara Barat also found out Anophels farauti larva live on fresh water or brackish water habitat. While two other species only found on fresh water habitat.…”
Section: Resultsmentioning
confidence: 89%
“…The most proper way to eliminate DHF vector is known as Behavior Eradication Mosquito Nest/Pemberantasan Sarang Nyamuk (PSN). It is a way to control the vector as one of the effort to prevent the infection of DHF (Sandy, 2017). The PSN campaign is encouraged by the government through Ministry of Health with 3M motto which mean to clean the water reservoir regularly, to close the water containers properly and to burry the waste goods able to be used by mosquito as nest (Arsin, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…9 Survei vektor malaria yang dilakukan pada tahun 2015 di Kabupaten Maluku Tenggara Barat dan penelitian yang dilakukan di Kabupaten Maluku Barat Daya pada tahun 2016 ditemukan sumber penularan malaria lebih banyak terjadi di areal perkebunan. 10 Survei terhadap nyamuk dilakukan di lingkungan perkampungan penduduk tidak ditemukan adanya nyamuk Anopheles spp. yang tertangkap, namun kebanyakan yang ditemukan spesies Culex spp.…”
Section: Pendahuluanunclassified
“…Bekas tempurung kelapa sisa hasil kegiatan pembuatan kopra berpotensial sebagai habitat perkembangan nyamuk di musim penghujan. 10 Pencegahan penularan terhadap tingginya angka kesakitan malaria oleh dinas kesehatan setempat dilakukan dengan membagikan kelambu LLINs ke masyarakat.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation